A genetic perspective of Metformin induced Vitamin B12 deficiency in Type 2 Diabetes mellitus patients - Cassinadane, Ananda Vayaravel; Ramaswamy, Ramesh; Govindarajan, Radhika; Srinivasan, Abu Raghavan (Asian Journal of Medical Sciences, 2018)
Metformin, a commonly prescribed hypoglycemic agent is a first line medication for the management of Type 2 diabetes mellitus. Numerous studies have depicted that metformin therapy has been associated with vitamin B12 and folate deficiency. Vitamin B12 deficiency is frequently missed or misdiagnosed by the clinicians because it is not routinely tested by most of the physicians, further the low end of the laboratory reference range is too low and misinterpreted as diabetic peripheral neuropathy. Vitamin B12 deficiency is a silent epidemic with serious consequences. Long term use of metformin has been associated with increased homocysteine levels and malabsorption of vitamin B12 leading to its deficiency and neurological manifestations. Polymorphisms of certain genes associated with the metabolism of vitamin B12 and folate might help in predicting the deficiency status of vitamin B12. Asian Journal of Medical Sciences Vol.9(1) 2018 11-14